The “Tatarstan Model”: Shaimiyev’s Authoritarianism and Russia’s Power Vertical - Martin Konstantinov (Bulgarian Journal of International Economics and Politics)
During the 1990s and early 2000s the Tatarstan Model was a key framework in Russia’s federal system, based on a power-sharing arrangement with Moscow, granting it more autonomy over its economy, culture, and policies, while still maintaining allegiance to the central government. The primary purpose of this paper is to critically analyze the Tatarstan model of governance during the four terms as president of the Republic of Tatarstan (RT) of Mintimer Shaimiyev (1991-2010). This model exemplifies a unique blend of authoritarian leadership, regional elite management, and crony capitalism. By examining how these elements interact within the context of Tatarstan, the paper aims to illuminate the implications for regional autonomy, economic development, and political stability in Russia. Based on an extensive review of theoretic literature, archival, local and national press sources, the present research employs a mixed-methods approach combining case-study, process-tracing and historical institutional analysis to examine Shaimiyev’s rule in Tatarstan. The paper details and provides evidence for the relevance of the main pillars of the TM, that have been major sources of stability for both the Tatarstan political establishment, and the RF’s “vertical of power” under Putin. Conclusions are drawn as to the crucial historic role of the Model for the overall vitality of the centre – regions power vertical in Russia.